2019
DOI: 10.1002/cssc.201802577
|View full text |Cite
|
Sign up to set email alerts
|

Green Hydrogen Separation from Nitrogen by Mixed‐Matrix Membranes Consisting of Nanosized Sodalite Crystals

Abstract: Nanosized sodalite (Nano‐SOD) crystals were used as active filler to prepare mixed‐matrix membranes (MMMs) for promoting the H2/N2 gas‐separation performance. The Nano‐SOD crystals with extremely small crystallites (40–50 nm) were synthesized from a colloidal suspension free of organic structural directing agent and uniformly dispersed in the polyetherimide (PEI) matrix. The Nano‐SOD filler with a suitable aperture size (2.8 Å) allowed only H2 molecules to pass through and rejected the N2, thus improving the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 27 publications
(8 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…Herein, we propose a novel homogeneous MOFs-MMMs membranes based on the combination of HKUST-1 nanocrystals and PEI. PEI, commercially known as ULTEM, is a high-performance thermoplastic polymer with imide, isopropylidene and ether groups [26,27]. It is cheap, has a good chemical and heat resistance as well as a good processability.…”
Section: Introductionmentioning
confidence: 99%
“…Herein, we propose a novel homogeneous MOFs-MMMs membranes based on the combination of HKUST-1 nanocrystals and PEI. PEI, commercially known as ULTEM, is a high-performance thermoplastic polymer with imide, isopropylidene and ether groups [26,27]. It is cheap, has a good chemical and heat resistance as well as a good processability.…”
Section: Introductionmentioning
confidence: 99%
“…It was found that ammonia started to crack when the temperature reached 473.15 K and the conversion efficiency can reach 98-99% when the temperature up to 698.15 K (Klerke et al, 2008;Lan et al, 2012). What's more, in contrast to co-firing hydrogen, using partially cracked ammonia is more economical and easier to implement (Yang et al, 2019). However, the deep insight into the combustion characteristics of NH 3 /H 2 /N 2 mixtures are limited (Mei et al, 2021;Wiseman et al, 2021).…”
Section: Frontiers In Energymentioning
confidence: 99%
“…64,84,85,88,190,191 ) several template free nanocrystals with SOD, FAU, RHO, CHA and EMT framework structures. 160,[192][193][194] The seeding-secondary growth method of zeolite membranes (seed dispersion, support modification and optimization strategy of mother solution) can be transferred to the preparation of MOF membranes as well. Compared with zeolite, the post-treatment step is easier for MOFs, the pores of most MOFs can be activated at mild condition (temperature below 100 o C).…”
Section: Seeding-secondary Growth Approachmentioning
confidence: 99%